Experiences and Insights from the Early US COVID-19 Epicenter: A Rapid Assessment Procedure Informed Clinical Ethnography Case Series. Issue 2 (2nd April 2020) - Moloney, Kathleen; Scheuer, Hannah; Engstrom, Allison; Schreiber, Merritt; Whiteside, Lauren; Nehra, Deepika; Walen, Mary Lou; Rivara, Frederick; Zatzick, Douglas
Abstract : Objective: The Coronavirus disease (COVID-19) outbreak has evolved into a pandemic crisis, with King County in Washington State emerging as the early US epicenter. A literature review revealed few reports providing front-line clinical and research teams guidance related to multilevel, rapidly evolving COVID-19 directives. Method: The Rapid Assessment Procedure Informed Clinical Ethnography (RAPICE) method was used to develop a clinical case series and conduct participant observation during an ongoing comparative effectiveness trial of peer-integrated, patient-centered interventions after traumatic injury. Participants were patients enrolled in the intervention arm of the ongoing trial, as well as front-line clinicians, patient peer interventionists, and clinical research team members implementing the trial. All participants were exposed to the Washington State COVID-19 outbreak. Results: Primary and secondary COVID-19 prevention strategies were feasibly integrated into ongoing care coordination and behavioral interventions for at-risk patients. Beyond the compilation of case studies, as an iterative method, RAPICE data collection naturalistically evolved to include observations of intervention team activity occurring within the larger pandemic epicenter context. A daily clinical research team huddle that flexibly accommodated virtual participation was also feasibly implemented. Conclusions: Primary and secondary COVID-19 prevention strategies can be feasibly integrated into ongoing clinical interventions during the pandemic. Routine, proactive clinical and research team communication that transparently addresses ethical tensions and health-sustaining activities may promote well-being for providers grappling with rapidly evolving pandemic directives. Proactive assessments of individual provider vulnerabilities for severe COVID-19 related respiratory illness may also be a crucial element of the health care system pandemic responses.